Migration and asylum in global education policies and debates: An approach to the discourses on mobilities and its subjects - Magalhães, Giovanna Modé; Schilling, Flavia (Education Policy Analysis Archives, 2021)
Considering the increased presence of immigrants and refugees in schools, particularly public schools, educational systems emerge as a field of research, policy and practice to understand the different discourses regarding contemporary mobilities. In this piece of work, our concern was to understand on which extension global education policies and debates, even being incipient on this matter, interact, reinforce or contradict the different practices, representations and sayings that make mobilities and their subjects an object of regulation and knowledge. We seek to observe the mobilized discourses, in order to fundamentally understand how they are articulated to the paradigm of global migration “as a problem” to overcome, instead of a constitutive characteristic of the world. As methodological strategy, we analyzed a recent set of documents guiding educational policies that deals with migration and asylum, written by different United Nations agencies. From this set, we highlight two central aspects for reflection: in a broader way the treatment given to individual and collective subjects of mobilities, and as a second axis we focused on the way the “figure of the victim” is built and reinforced, as well as its implications, tensions and ambiguities.